Mystical tradition in Sampaio Bruno - Lázaro Pulido, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Sampaio Bruno (1857-1915) in one of the most important cultural authors in Porto and the rest of Portugal. His philosophical and religious thought, especially his mystical conception, can be inscribed in the last romanticism. The Sampaio Bruno’s mysticism expresses the romanticism in an eclectic, antimetaphysical, and gnostic reading of the philosophical tradition. This reading, moreover, affirms the richness of the tradition itself in the infinity search.